Analysis of the Effect of Structural Transformation of The Economy - Nasution, Armin Rahmansyah; Wulandari, Maya; Hasugian, Fitrah Maya Sari; Dachi, Indriana; Hasibuan, Alawi Parlindungan; Maulana, Juanda; Muntaza, Kaiesa Raihatul (LPPPIPublishing, 2024)
This study aims to analyze the impact of economic structural transformation on economic growth, income inequality, labor distribution, and community welfare. The method used is a literature study, by reviewing various academic literature, government agency reports, and case studies of countries that have undergone structural transformation. The results show that economic structural transformation generally increases economic growth and productivity through labor shifts from the primary sector to the secondary and tertiary sectors. These sectors tend to be more productive and efficient, resulting in increased output and new economic opportunities. However, these positive impacts are often accompanied by rising income inequality, as the industrial and service sectors offer higher compensation than the primary sector. In addition, this transformation brings significant changes to labor market dynamics, requiring new skills that the primary sector workforce may not possess, thus risking increased unemployment and skills gaps. From a social perspective, the structural transformation of the economy may lead to lifestyle changes and rapid urbanization, leading to infrastructure stress and social disintegration. To address these challenges, the study recommends a range of policies, including training and education programs that focus on inclusion, as well as income redistribution policies to reduce inequality. In conclusion, the structural transformation of the economy presents significant growth opportunities, but requires an inclusive and sustainable strategy to ensure its impact is felt equally across society. This study provides relevant recommendations for policymakers in managing economic structural transformation with a balanced approach between growth and social inclusion.